Understanding Cancer Through the Lens of Epigenetic Inheritance, Allele-Specific Gene Expression, and High-Throughput Technology - Lee, Maxwell P. (Frontiers in Oncology, 2019)
Epigenetic information is characterized by its stable transmission during mitotic cell divisions and plasticity during development and differentiation. This duality contrasts to genetic information, which is essentially static and identical in every cell in an organism except immunoglobulin gene rearrangements in lymphocytes and mutations in cancer cells. Allele-specific analysis of gene expression and epigenetic modifications provides a unique approach to studying epigenetic regulation in normal and cancer cells. Extension of Knudson’s two-hits theory to include epigenetic alteration as a means to inactivate tumor suppressor genes provides better understanding of how interplay between genetic mutations and epigenetic alterations contributes to cancer development. High-throughput technology has greatly accelerated cancer discovery. Large initiatives such as TCGA have shown that epigenetic components are frequent targets of mutations in cancer and these discoveries provide new insights into understanding cancer etiology and generate new opportunities for cancer therapeutics.